PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN BAHASA JAWA SERANG DI SEKOLAH DASAR - Putri, Shafira Meidifa; Yuliana, Rina; Setiawan, Sigit (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to develop a local wisdom-based scrapbook learning media to support fourth-grade students at SD Negeri Curug, Serang City, in learning Javanese language, particularly the Baguse Sesarengan material. The study describes the development process, media feasibility, and students’ responses. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation results showed that the media received a score of 93.6% (very feasible), material validation scored 98.3% (very feasible), and language validation scored 93% (very feasible), resulting in an overall score of 94.8% categorized as “Very Feasible.” Student responses to the learning media reached 96.6%, categorized as “Very Good.” The findings indicate that the local wisdom-based scrapbook learning media is highly feasible, effective, and positively received by students, making it a suitable tool for enhancing the Javanese language learning experience.